PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE PRACTICE REHEARSAL PAIRS DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 SIPORA KABUPATEN KEPULAUAN MENTAWAI - Rahayu, Ika Fitri; Rahmi, Rahmi; Haryono, Yulia (STKIP PGRI Sumbar, 2014)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTThe purpose of this research was to reveal whether the Â by the mathematics understanding of the students taught by Practice Rehearsal Pairs active learning strategy was better than that of students taught by using conventional learning. This was an experimental research. The population of this research was the students in class VIII of SMPN 1 Sipora Kabupaten Kepulauan Mentawai registered in academic year 2013/2014. The instrument of the research was a test Â whose reliability 0,847. Based on the result of data analysis it was figured out that the average score of the studentsâ conceptual Â understanding in the experimental class was 75,80 and in the control class was 64,98. The result of hypothesis test showed that P-value (0,005) was smaller Î± = 0,05, therefore it was concluded that the mathematics conceptual understanding of the students taught by using Practice Rehearsal Pairs active learning strategy was better than that of students taught by using conventional learning students in classVIII Â SMPN 1 Sipora Kabupaten Kepulauan Mentawai.